Dynamic Shift Coordinated Control Based on Motor Active Speed Synchronization with the New Hybrid System. (11th July 2017) - Yan, Ting; Yang, Lin; Yan, Bin; Zhou, Wei; Chen, Liang; Zhou, Wei
Abstract : Considering the inherent disadvantages that severely affect driving comfortability during the shift process in HEVs, a dynamic shift coordinated control based on motor active speed synchronization is proposed to improve shift quality by reduction of shift vibration. The whole control scheme is comprised of three phases, preparatory phase, speed regulation phase, and synchronization phase, which are implemented consecutively in order. The key to inhibiting impact and jerk depends on the speed regulation phase, where motor active speed synchronization is utilized to reach the minimum speed difference between the two ends of synchronizer. A new hybrid system with superior performances is applied to present the validity of the adopted control algorithm during upshift or downshift, which can represent planetary gear system and conventional AMT shift procedure, respectively. Bench test, simulation, and road test results show that, compared with other methods, the proposed dynamic coordinated control can achieve shifting control in real time to effectively improve gear-shift comfort and shorten power interruption transients, with robustness in both conventional AMT and planetary gear train.